(untitled) (Kronika Bydgoska, 2010)
The first ten years of the activity of the Polish Radio Station in Bydgoszcz are connected inseparably with Arnold Rezler. He was one of its organisers and the manager of the Program Department. In 1945, he formed a musie group, which soon won nationwide famę as the Bydgoszcz Radio Station Orchestra. The greatest artists performed with the orchestra, and their concerts were broadcast from Bydgoszcz to Prague, Budapest, Berlin, and Paris. Starting from 1946, Rezler managed also the Pomeranian Symphony Orchestra. Musicians from these groups were the hard core of the Pomeranian Philharmonic established in 1953.